2021
DOI: 10.3892/etm.2021.10064
|View full text |Cite
|
Sign up to set email alerts
|

Subacute toxicological evaluation of AT‑533 and AT‑533 gel in Sprague‑Dawley rats

Abstract: As a novel heat shock protein 90 inhibitor, AT-533 exhibits various biological activities in vitro, including anti-viral, anti-tumor and anti-inflammatory activities. Moreover, AT-533 gel, a gel dosage form of AT-533, has been suggested to have anti-keratitis and herpes simplex virus type-1 infection-induced effects on the skin lesions of animals. However, the safety evaluation of AT-533 and AT-533 gel has, to the best of our knowledge, not been examined in in vivo toxicological tests. Therefore, these toxicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Ninety specific pathogen‑free (SPF) male and female 6-8-week old SD rats were obtained from the Experimental Animal Center of Southern Medical University (Guangzhou, China) under the license number SCXK(YUE)20160041. Feeding conditions are consistent with what we described earlier [ 26 ]. Simply, every 5 rats was kept in a plastic cage with labels attached for identification.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…Ninety specific pathogen‑free (SPF) male and female 6-8-week old SD rats were obtained from the Experimental Animal Center of Southern Medical University (Guangzhou, China) under the license number SCXK(YUE)20160041. Feeding conditions are consistent with what we described earlier [ 26 ]. Simply, every 5 rats was kept in a plastic cage with labels attached for identification.…”
Section: Methodssupporting
confidence: 88%
“…20180520) and AT-533 gel (Lot No. 20180706) were acquired according to previous reports [ 25 , 26 ]. AT‑533 was dissolved in propyleneglycol, PEG400 and sterile water for skin absorption.…”
Section: Methodsmentioning
confidence: 99%
“…The use of certain chemical compounds that can modulate the chromatin state of the viral genome resulting in the enhancement of antiviral immunity or suppression of infection and recurrence is another option; novel therapeutic techniques such as CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats) have significant potential to make changes in the latent viral DNA in sensory neurons and as such cure the neuronal location of the infection[ 328 - 333 ]. Wu et al [ 334 ] have also reported on AT-533, a heat shock protein-90 antagonist that expressed inhibitory effects on HSV keratitis.…”
Section: Novel Therapeutic Approaches For Herpes Simplex Keratitis: C...mentioning
confidence: 99%